Robust and accurate visual echo cancellation in a full-duplex projector-camera system - Liao, Miao (IEEE transactions on pattern analysis and machine intelligence, 2008)
In this paper we study the problem of "visual echo" in a full-duplex projector-camera system for telecollaboration applications. Visual echo is defined as the appearance of projected contents observed by the camera. It can potentially saturate the projected contents, similar to audio echo in telephone conversation. Our approach to visual echo cancellation includes an offline calibration procedure that records the geometric and photometric transfer between the projector and the camera in a look-up table. During run-time, projected contents in the captured video are identified using the calibration information and suppressed, therefore achieving the goal of cancelling visual echo. Our approach can accurately handle full-color images under arbitrary reflectance of display surfaces and photometric response of the projector or camera. It is robust to geometric registration errors and quantization effects and is therefore particularly effective for high-frequency contents such as texts and hand drawings. We demonstrate the effectiveness of our approach with a variety of real images in a full-duplex projector-camera system